Mucosa-associated lymphoid tissue lymphoma in conjunctiva - Mondal Santosh (Wolters Kluwer Medknow Publications, 2008)
A case of primary mucosa-associated lymphoid tissue (MALT) lymphoma (marginal zone B-cell lymphoma of MALT according to WHO classification) in conjunctiva, which presented as a slowly growing salmon-colored mass at limbus of left eye is reported. Histological examination revealed a diffuse low-grade lymphoma. Immunohistochemical analysis using monoclonal antibodies showed that the tumor cells are leukocyte common antigen (CD45)+, CD20+, CD3−, CD5−, CD10− and CD43−, which confirmed the B-cell lineage of lymphoma. The case is being reported for its rarity and clinical importance of recognizing such cases because of excellent prognosis.